Assessment and Implementation of WOAH Day 1 Competencies (AID-1C): a cyclical methodology for curriculum harmonization with international standards - Hoet, Armando E.; Swisher, Samantha; Berrian, Amanda M.; Bessler, Andrea L.; Grozdic, Ivana (Frontiers in Veterinary Science, 2024)
The World Organisation for Animal Health (WOAH) Day 1 Competencies for Graduating Veterinarians provide a standard framework to guide Veterinary Educational Establishments (VEE) in improving their veterinary public health and population medicine curricula. However, pursuing a curriculum revision to incorporate these standards may be daunting, especially for institutions with limited resources or experience. This manuscript describes a methodology for targeted curriculum revision specifically focused on the WOAH Day 1 Competencies. Phases of the AID-1 Process: The Assessment and Implementation of WOAH Day 1 Competencies (AID-1C) is a six-step, cyclical, collaborative methodology that encompasses a series of tools and processes that help a VEE to evaluate their curriculum, identify and prioritize gaps, and develop and implement an action plan based on the results. The six phases of the AID-1C process include: 1) Assessment of the proficiency of the VEE's graduates in Day 1 Competencies using a structured Evaluation Tool; 2) A systematic curricular review and evaluation; 3) Identification and prioritization of interventions through a group problem-solving and prioritization exercise called Focus Forward; 4) Design and development of interventions to address identified gaps; 5) Curricular implementation; and 6) Monitoring and evaluation. The AID-1C methodology relies upon active involvement of senior students, recent graduates, faculty, instructional staff, and employers throughout the process.The AID-1C methodology provides a systematic, participatory, collaborative approach that simplifies the planning and execution of the curricular revision, making a complex process more manageable. This enables VEEs to improve their curricula, while moving towards harmonization with WOAH standards. The result is a curriculum that allow a VEE to train well-rounded and competent veterinarians, with the requisite skills to support the veterinary services in their country.